Evaluating the Extent to Which the Colors Used in the Illustrations in Children's Picture Books Have a Positive Effect on the Intellectual Development of Young Children - Song, Shangyu (International Journal of Computer Science and Information Technology, 2024)
Children's picture books have become the first choice for reading books because young children cannot understand anything too complicated. A picture book is a book that closely interweaves images, illustrations, colors, and text to tell a story about a specific theme. This paper will demonstrate the positive effects of bright colors used in picture book illustrations on young children's color perception and language organization skills, and demonstrate that these positive effects lead to differences in color preferences and effects between 7–9-year-old boys and girls when viewing colors in picture book illustrations.